Efficacy, explore, and exchange: Studies on social side of teacher education from England, Spain, and US. (2020) - Liou, Yi-Hwa; Daly, Alan J.; Downey, Christopher; Bokhove, Christian; Civís, Mireia; Díaz-Gibson, Jordi; López, Susana
Highlights: Self-efficacy is associated with seeking instructional materials from peers across settings. Exchanging new ideas plays an important role in seeking materials from peers across settings. Peer trust plays a significant role in the seeking behaviors within the English cohort. Abstract: This study attempts to respond to a recent call for a more social and collaborative approach to teacher education and professional development by examining the social side of pre-service teachers during preparations from England, Spain and US. We explore core factors that are associated with dyads of pre-service teachers in exchanging instructional materials at the end of a teacher education program from each setting. Using social network selection models, this study investigates the extent to which pre-service teachers' reported self-efficacy, peer trust, innovativeness, and demographic characteristics is associated with the sending, receiving, and reciprocating instructional materials. Findings suggest the important role of self-efficacy and innovativeness in explaining pre-service teachers' seeking behaviors across the study contexts.